Performance Of Athulya Strain Under Kerala Climatic Condition - Ponnuvel , P.; Narayanankutty , K. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
An attempt was made to find out the production performance of the Athulya strain for commercial farming. Two hundred Athulya strain were used to study the production potential from 20 to 40 weeks of age at farm condition at AICRP, Mannuthy. The body weight at 20 and 40 week were 1.42 and 1.75 kg respectively and average hen housed egg production was 91.34 per cent. The egg weight at 40 week was 55.06 gram and the overall livability of 99.5 percent was recorded with a mean daily feed intake of 114.67 grams and mean FCR per dozen of egg was 1.56.
Keywords: Athulya; White Leghorn; egg production